When the moon turns blue : a novel - Terry, Pamela, 1956- (Ballantine Books, 2023)
"One woman fights to hold on to her friends, her family, and all that she holds dear as the battle over a Confederate statue divides her small-town Georgia community in this powerful novel from the author of The Sweet Taste of Muscadines. On the morning after Harry Cline's funeral, a rare ice storm hits the town of Wesleyan, Georgia. The community wakes up to find its controversial statue of Confederate general Henry Benning destroyed-and not by the weather. Half the town had wanted to remove the statue; the other half wanted to celebrate it. Now that the matter has been taken out of their hands, the town's long-simmering tensions are laid bare. Without Harry beside her, Marietta is left to question many of her preconceived ideas about her friends and family. Her childhood friend, Butter, has come to her aid in ways Marietta never expected, or asked for. Her sister-in-law, Glinda, is behaving completely out of character, and her brother, Macon, the top defense attorney in the Southeast, is determined to find those responsible for the damage to the statue and protect the legacy of Old Man Griffin, the owner of the park where it stood. Marietta longs to salvage these connections, but the world is changing and the divides can no longer be ignored. With a cast of poignant, relatable characters, When the Moon Turns Blue is a compassionate and timely novel about family, friendship, and what can happen when we discover that we don't particularly like the people we love"--